(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2020)
In this study, twenty-two new [1,2,4]triazolo[3,4-b][1,3,4]thiadiazoles (5a-n, 6a-h) were synthesized under microwave irradiation (MWI). The chemical structures of the compounds were elucidated by their IR, 1 H-NMR, LC-MS, and elemental analysis. The compounds were tested for antinociceptive activity by using the tail clip, tail flick, hot plate, and writhing methods in mice. The varying levels of antinociceptive activity of the compounds were compared with those of aspirin. Among these compounds, compound 5g and 5j were found to be significantly more active than the other compounds and the standard in the tests. Also, inhibitory effects of the test compounds on COX-1 and COX-2 activities were investigated. DuP-697 for COX-2 and SC-560 for COX-1 were used as reference standards.